IoT hardware from prototype to production - Marshall, Richard; Archard, Lawrence; Hodges, Steve (Digital Catapult, 2019)
This guide has been devised to support startups and scale-ups who are developing IoT hardware products. By stepping through the product lifecycle process the document provides a starting point for businesses to understand the challenges and activities involved in launching an IoT product. There is much more to know and to learn along the IoT product journey that cannot be simply captured in a single document; we have therefore provided a set of references at the end of this document for useful further reading. We hope that the guide will help you on the road to success and we wish you the best of luck with your IoT hardware endeavours.